Development of a diagrammatic scale for the quantification of entomosporiosis (Diplocarpon mespili) in quince - Nogueira, Carolina Carvalho Almeida (2017)
Quince (Cydonia oblonga) is appreciated around the world for its uses in the jam and jellie industries. It also has interesting antibiotic and antioxidant properties that may be further exploited. Although its production does not stand out economically, the quince has been considered an "emergent fruit". This is due to its adaptation to acid soils and high temperatures which makes possible its cultivation in regions that are unsuitable for the cultivation of more demanding crops. Quince production is hampered by Diplocarpon mespili, a fungus that causes leaf spots, leading to defoliation and low productivity levels. Little is known about the fungus in associtation with quince. In this study, the first chapter presents a theoretical background about entomosporiosis. The second chapter demonstrates the elaboration, validation and comparison of two new diagrammatic scales for quantification of entomosporiosis in quince and the evaluation of the resistance of 29 quince cultivars to the disease. The scales were elaborated in different ways. One of them was structured with six levels, each level (with the exception of level 0) represents a range of disease severity and is illustrated with three images, totaling 16 illustrations. The other was structured as a percentage of diseased area (without levels) and has six illustrations. The elaborated scales were validated with Lin's statistics and linear regression. Although the Lin’s statistics did not show a significant difference between the scales, the linear regression indicated a slightly better accuracy of the diagrammatic scale with levels. The resistance of quince cultirvares evaluation showed that Japanese cultivar is the most resistant, while Rea's Mamouth is the most susceptible.